Psychoneurological symptom clusters in patients with first stroke and relationship with inflammatory markers: a latent profile analysis - Tang, Yuanyuan; Jiang, Gudi; Jin, Meilan; Wu, Shanyu; Wu, Jinji (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to explore the relationship between psychoneurological symptom clusters and inflammatory markers in patients with a first stroke.MethodsThis study investigated 227 patients with a first stroke using general information questionnaires, Numerical Rating Scale, Pittsburgh Sleep Quality Index, Hospital Anxiety and Depression Scale, Ascertain Dementia 8, Fatigue Severity Scale, and Stroke-Specific Quality of Life. Data analysis included latent profile analysis, one-way analysis of variance, and unordered multicategorical logistic analysis.ResultsThe psychoneurological symptom clusters of first-stroke patients were categorized into three latent profiles: the low symptom group (45.2%), moderate symptom group (36.7%), and high symptom group (18.1%). Logistic regression analyses showed that younger age, female, higher National Institute of Health Stroke Scale score, higher interleukin-6 level, and higher hypersensitive C-reactive protein level were major predictive factors for the moderate and high symptom groups.ConclusionThree latent profiles of psychoneurological symptom clusters exist in patients with a first stroke and are associated with markers of inflammation (interleukin-6 and hypersensitive C-reactive protein), thereby affecting their quality of life. These findings extend previous research on psychoneurological symptom clusters in stroke. Further exploration of a broader range of inflammatory markers and psychoneurological symptom clusters is necessary to advance symptom management.